Solithromycin inhibits IL-13-induced goblet cell hyperplasia and MUC5AC, CLCA1, and ANO1 in human bronchial epithelial cells - Kimura, Yasuhiro; Shinoda, Masahiro; Shinkai, Masaharu; Kaneko, Takeshi (PeerJ, 2023)
Solithromycin is a novel fluoroketolide antibiotic belonging to the class of macrolide antibiotics. Activation of the interleukin (IL)-13 receptor leads to STAT6 activation and subsequent induction of SAM pointed domain containing ETS transcription factor (SPDEF), chloride channel accessory 1 (CLCA1), and anoctamin-1 (ANO1), all of which are associated with the induction of MUC5AC. We examined the effects of solithromycin on mucin production led by IL-13 signaling. Normal human bronchial epithelial cells were grown at the air-liquid interface with IL-13 with/without solithromycin for 14 days. Histochemical analysis was performed using hematoxylin and eosin staining and MUC5AC immunostaining. MUC5AC , SPDEF , CLCA1 , and ANO1 mRNA expressions were examined using real-time polymerase chain reaction. Western blot analysis was performed to assess CLCA1 and ANO1 proteins, and phosphorylation of STAT6 and ERK. Solithromycin attenuated IL-13 induction of goblet cell hyperplasia and MUC5AC , CLCA1 and ANO1 mRNA and protein expression induced by IL-13, but had no effect on the phosphorylation of STAT6 and ERK. Our results indicate that solithromycin could attenuate goblet cell hyperplasia and MUC5AC induced by IL-13 through inhibition of CLCA1 and ANO1 mRNA and protein expression. However, much more information is required to clarify the molecular mechanisms underlying the inhibition of CLCA1 and ANO1 by solithromycin.